Experience of phakic lens implantation for the correction of myopia and astigmatism: feature of preoperative examination and lens parameters - B.V. Laptev; A.B. Lapteva; A.Ya. Renzyak (Офтальмохирургия)
Purpose. To evaluate postoperative vault parameters – from the posterior surface of the phakic posterior intraocular lens (PIOL) to the anterior surface of the lens, its correlation with the preoperative data study and the choice of the PIOL size. Material and methods. This research was based on the retrospective analysis of 128 eyes (64 patients) for the period from February 2019 to May 2021. The age of patients varied from 21.0 to 42.0 29.5±5.5 (mean 29.5±5.5) years. All patients underwent PIOL implantation with Staar EVO Visian ICL (V4C) PIOL. The follow-up period ranged between 3 to 24 months. Associations between the postoperative vault and age, ICL size, spherical equivalent (SE), axial length (AL), anterior chamber depth (ACD), white-to-white (WTW) were investigated using Spearman’s correlation analysis and stepwise multiple regression analysis.Accepted confidence level p<0.05. Results. The mean values of the vault were from 142 to 1340 μm (576,56±245,77 μm). Statistical analysis revealed that the postoperative vault height had a moderate correlation with WTW, IOL size and ACD (anterior chamber depth). There was no significant correlation with age, spherical equivalent, axial length. There was a strong correlation between PIOL’s size and WTW, and a significant correlation with ACD. Stepwise multiple regression showed that ICL size, anterior chamber depth, WTW were significant factors associated with postoperative vault (adjusted R2 0.359). Conclusion. The assessment of the size of the postoperative vault and its dependence on the data of the preoperative study showed that the size of the PIOL and the depth of the anterior chamber have the greatest influence on the formation of the postoperative vault. Optimal postoperative vault was achieved in 86% cases. In conclusion, the currently existing method for PIOL sizing does not always yield ideal vault. In some cases, it is necessary to choose a smaller PIOLs size to obtain the optimal vault.